PATHWAY TOWARDS CARBON NEUTRALITY FOR THE PUBLIC UNIVERSITY IN SARAWAK, BORNEO - Muhammad Syukri Imran, Abdullah; Azhaili, Baharun; Lidyana, Roslan (Taylors University, 2026)
The push for sustainability in higher education institutions increasingly focuse on net-zero carbon emission buildings (NZEBs) as a key strategy for reducing carbon footprints. This study evaluates the feasibility of achieving net-zero carbon emissions within the Engineering Faculty at Universiti Malaysia Sarawak (UNIMAS). A digital energy model of the faculty was created using IES-ICD software to simulate baseline performance and assess various retrofit and renewable energy options. The method involved detailed energy modelling, analysis of local climate data, estimation of rooftop solar photovoltaic (PV) generation potential, and projection of grid decarbonization trends through 2050. Energy efficiency measures - such as building envelope insulation, lighting upgrades, and HVAC optimization - were implemented alongside phased solar PV installations under the Net Energy Metering (NEM) scheme. These measures are expected to reduce Building Energy Intensity (BEI) from 146 to 107 kWh/m²/year and lower site carbon emissions from 1,637 to 711 tons CO₂e annually by 2050. The study alsoexplores the use of Power Purchase Agreements (PPAs) and Renewable Energy Certificates (RECs) to overcome regulatory and technical barriers to self-consumption systems. The results suggest that a combined approach of targeted retrofits, on-site renewable energy, and carbon offsetting offers a technically and financially feasible pathway to net zero emissions, serving as a replicable model for institutional buildings across Malaysia’s tropical regions.